Trends of repeated emergency department visits among adolescents and young adults for substance use: A repeated cross-sectional study - Soyeon Kim; John Weekes; Matthew M. Young; Nicole Adams; Nathan J. Kolla (PLoS ONE, 2023)
Emergency Department (ED) visits for substance-related concerns among young people have been increasing in recent years. Understanding the factors related to repeated ED visits (two or more ED visits per year) for substance use concerns among young people is critical to developing a more efficient mental healthcare system that does not overburden ED and that provides efficient care for substance use patients. This study examined trends of substance use-related ED visits and factors related to repeated ED visits (two or more ED visits per year, in comparison to one ED visit per year) among adolescents and young adults (aged 13 to 25 years) in the province of Ontario, Canada. Binary logistic regression models were conducted to examine associations between hospital-related factors (hospital size, urbanicity, triage level, ED wait time) and visit status (2+ vs 1 ED visit/year), controlling for patient characteristics (age/sex). A population-based, repeated cross-sectional data over a 10-year period (2008, 2013, and 2018) was used. The proportion of substance use-related repeated ED visits significantly and consistently increased in the year 2013 and 2018 compared to 2008 (2008 = 12.52%, 2013 = 19.47%, 2018 = 20.19%). Young adult, male, medium-sized hospital, urban location, wait times longer than 6 hours, and symptom severity was associated with increased numbers of repeated ED visits. Furthermore, polysubstance use, opioid use, cocaine use, and stimulant use were strongly associated with repeated ED visits compared with the use of substances such as cannabis, alcohol and sedatives. Current findings suggest that repeated ED visits for substance use concerns could be reduced by policies that reinforce evenly distributed mental health and addiction treatment services across the provinces in rural areas and small hospitals. These services should put special efforts into developing specific (e.g., withdrawal/treatment) programming for substance-related repeated ED patients. The services should target young people using multiple psychoactive substances, stimulants and cocaine.